PROLAPSE OF UTERUS AND ABDOMINAL VISCERA WITH VAGINAL TE~R IN A BUFFALO - SELVARAJU, M; KULASEKAR, K; SUBRAMANIAN, M; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
Prolapse of uterus and abdominal viscera with vaginal tear in a buffalo.is reported.
Keywords: Uterus; Vagina; Abdominal viscera; Buffalo